Biopreservation approaches to reduce Listeria monocytogenes in fresh vegetables - Ramos, Bárbara (2019)
Two biopreservation approaches for fresh lettuce, rocket salad, parsley and spinach were studied. The potential of Pediococcus pentosaceus DT016, as a protective culture, to suppress Listeria monocytogenes in vegetables during storage was evaluated. The pathogen numbers in the vegetables inoculated with P. pentosaceus DT016 were significantly (p < 0.01) lower throughout the storage period and, at the last storage day, a minimum difference of 1.4 log CFU/g was reported when compared with the vegetables without the protective culture. Moreover, by using two levels of L. monocytogenes (about 6 and 4 log CFU/g), it was observed that the antagonist effect of P. pentosaceus was higher for the lower pathogen numbers. The second approach evaluated a pediocin DT016 solution to inactivate and control L. monocytogenes proliferation. The pathogen load was studied after washing with: water, chlorine and the pediocin solution and along storage at 4  °C. Comparing the various washing solutions, the vegetables washed with pediocin presented significantly (p < 0.01) lower pathogen numbers throughout storage, by a minimum of 3.2 and 2.7 log CFU/g, than in vegetables washed with water and chlorine, respectively. The proposed methodologies are promising alternatives to maintain the safety of fresh vegetables during extended storage at refrigeration temperature.